Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
x = - 3
Step-by-step explanation:
y = 5 + [tex]\frac{1}{x+3}[/tex]
= [tex]\frac{5(x+3))+1}{x+3}[/tex] = [tex]\frac{5x+16}{x+3}[/tex]
The denominator of y cannot be zero as this would make y undefined
Equating the denominator to zero and solving gives the value that x cannot be and if the numerator is non- zero for this value then it is a vertical asymptote.
x + 3 = 0 ⇒ x = - 3
The vertical asymptote is x = - 3
Answer:
x = -3.
Step-by-step explanation:
The asymptotes occurs when the denominator x + 3 = 0,
- that is when x = -3.
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.